2013
DOI: 10.4314/ahs.v13i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality of critical care trauma patients

Abstract: Background: Critically-ill trauma patients have a high mortality. Objective: To study the factors affecting the mortality of ICU trauma patients treated at Al-Ain Hospital, United Arab Emirates (UAE). Methods: All trauma patients who were admitted to the ICU were prospectively collected over three years (2003)(2004)(2005)(2006). Univariate and multivariate analysis were used to compare patients who died and who did not. Gender, age, nationality, mechanism of injury, systolic blood pressure and GCS on arrival, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 15 publications
4
15
0
11
Order By: Relevance
“…Giacino and Kazanis concluded that GCS score in the first 24 hours was critical in predicting vital signs and functional results during the 2-3 day after the injury [4]. Studies has also show that impaired papillary reactivity have a good documented correlation with unfavourable outcome, duration of mechanical ventilation and length of stay [14] have an impact on the patients' outcome and QoL after an ICU stay [14,27] that is consistent with this study.…”
Section: Discussionsupporting
confidence: 79%
“…Giacino and Kazanis concluded that GCS score in the first 24 hours was critical in predicting vital signs and functional results during the 2-3 day after the injury [4]. Studies has also show that impaired papillary reactivity have a good documented correlation with unfavourable outcome, duration of mechanical ventilation and length of stay [14] have an impact on the patients' outcome and QoL after an ICU stay [14,27] that is consistent with this study.…”
Section: Discussionsupporting
confidence: 79%
“…ABD'de YBÜ yatışlarının %15'i travma nedeni ile gerçekleşmiş olup (9); ülkemizde yapılan bir çalışmada YBÜ'de izlenen 1038 hastanın 108'i travma nedeniyle çalışmamıza benzer olarak %10,4 oranında izlenmiştir (10). Multi-travmalar yüksek mortalite, post-travmatik bozukluk, fiziksel ve psikososyal sonuçları ile yaşam kalitesini etkileyen önemli bir problemdir; yüksek bir komplikasyon oranına neden olabileceği için hastaların travma izlemi için uygun olan YBÜ'de izlenmeleri gerekmektedir (11,12). Travma hastalarının YBÜ'ye kabulünde bu oransal değişkenlik farklı yoğun bakımlarda farklı travma oranları ile karşılaşılabileceğini ve travma izlemi için standardizasyon ihtiyacı doğurabileceğini göstermektedir.…”
Section: Discussionunclassified
“…Travmanın ciddiyetini belirlenmesi ve mortalite tahmini amacı ile birçok skorlama sistemi kullanılmaktadır (5,11,13). Yoğun bakım ünitelerinde travma hastalarının takibinde APACHE-2 gibi fizyolojik skorlama sistemleri veya RTS gibi klinik ve fizyolojik değerlendirmenin beraber yapılabildiği skorlama sistemleri sıklıkla tercih edilmektedir (28).…”
Section: Discussionunclassified
“…Hastaların median yaşları 44,5 ve %75,9'u erkek olarak tespit edildi. Medyan Glasgow Koma Skorları ölüm grubunda sağkalım grubuna göre daha düşük (5 (3-8) vs. 15 (13)(14)(15), p<0,0001), medyan APACHE II skorları daha yüksek (20 (15-26) vs. 10 (8-13), p<0,0001) ve median yatış süreleri daha uzun (27 (5-62,5) vs. 2 (1)(2)(3)(4)(5), p<0,0001) tespit edildi. En sık görülen travma etiyolojisi %47,2 oranda trafik kazası olup, hastaların %52,7'sinde kafa travması mevcut idi.…”
unclassified
“…Hastaların %38,9 eritrosit süspansiyonu, %27,8'i taze donmuş plazma, %0,9'u trombosit süspansiyonu ve %8,3'ü albümin almıştır. İnvaziv mekanik ventilasyon, %27,8 oranda yapılmış olup, median İMV süresi 5 (1,5) (13)(14)(15), p<0.0001), median APACHE II score was higher (20 (15-26) vs. 10 (8-13), p<0.0001) and median duration of ICU stay was longer (27 (5-62,5) vs. 2 (1-5), p<0.0001) than those in the survival group. The most common etiology of trauma was traffic accidents (47.2%) and 52.7% of patients had head trauma.…”
mentioning
confidence: 99%